Study of Logistic Transportation Based on The Movement of Agricultural Commodities In Aceh Province - Zafir Istawa Pramoedya; Hasna Nabila Kusuma Wicaksono; Syifa Fauziah; Dwi Novi Wulansari; Revy Safitri (Journal of Logistics and Supply Chain, 2022)
Transportation is still a problem in every region in Indonesia, including in Aceh Province. As the node of sea transportation, ports have an increasingly large role in economic development in line with the increasing importance of ports in logistical activities. This study aims to examine logistics transportation based on the movement of agricultural commodities in Aceh Province. The research method uses descriptive quantitative methods with a secondary data analysis approach. The data used in this study are data of the movement of goods and data on agricultural products in Aceh Province. The data analysis approach used linear regression and was validated through the coefficient of determination and correlation test as well as the t-test and ANOVA test. Based on the results of analysis and statistical validation, it can be seen that agricultural products have a positive and significant linear relationship with the generation of movement of goods in Aceh Province.